Factor decomposition analysis and causal mechanism investigation on urban transport CO2 emissions: Comparative study on Shanghai and Tokyo. (August 2017) - Luo, Xiao; Dong, Liang; Dou, Yi; Li, Yan; Liu, Kai; Ren, Jingzheng; Liang, Hanwei; Mai, Xianmin
Abstract: Low-carbon urban development has been regarded as a promising pathway for mitigating climate change, and the transportation sector makes a key contribution to a significant proportion of all CO2 emissions. Investigating the driving factors and analysing the causal mechanism on urban transport CO2 emissions is critical for stakeholders and policy-makers to draft appropriate policies for low-carbon transport, and conducting a comparative study on developed and developing countries' experiences will provide beneficial insights from an evolving perspective. To date, many emerging case studies have analysed urban transport CO2 emissions in China; however, they lack an in-depth decomposition and causal mechanism analyses as well as a comparative study. To fill this gap, this study aims to conduct a decomposition analysis and causal mechanism investigation study on the urban transport sector with comparative studies on two Asian mega cities, Tokyo and Shanghai. We illustrate the driving forces of the urban transport sector and the causal mechanism of each factor and provide critical policy insights through comparative studies. The outcomes of this study provide critical insights to recent practices in Shanghai as well as practical guidance to low-carbon urban planning in developing countries. Highlights: Conduct decomposition analysis on urban transport CO2 emission in Shanghai and Tokyo. Draw causality map on the urban transport CO2 emissions in Shanghai and Tokyo. Factors of Avoid, Shift and Improve on the urban transport are analysed. Experiences of Tokyo is discussed and propose implications for Shanghai.